3-Benzoyl-4H-chromen-4-one: A novel twisted acceptor for highly efficient thermally activated delayed fluorescence emitters. (December 2020) - Wang, Peng; Yu, Junsheng; Chen, Shanyong; Yu, Hong; Yan, Xingwu; Guan, Youwei; Chen, Jinlei; Li, Lu
Abstract: In this work, a novel twisted 3-benzoyl-4H-chromen-4-one (BZC) acceptor is reported and a BZC-based thermally activated delayed fluorescence (TADF) emitter, 3-(4-(10H-phenoxazin-10-yl)benzoyl)-4H-chromen-4-one (BZC-PXZ), is developed. The unique structure of BZC endows BZC-PXZ with favorable molecular and stacking structures. First, the small and twisted structure of BZC group not only brings about large dihedral angle (88.78°) between donor and acceptor groups, but also efficiently prevents π∙∙∙π interaction. Second, the three oxygen atoms of BZC group bring about abundant weak intermolecular interactions which can enhance the charge-transporting ability of BZC-PXZ and facilitate the exciton recombination on it. As a result, BZC-PXZ exhibits small singlet-triplet energy splitting (0.02 eV) and high photoluminescence quantum yield (93%) simultaneously. Meanwhile, the BZC-PXZ-based device displays high efficiency (64.6 cd/A, 69.0 lm/W, 21.3%), high exciton utilization efficiency (77.2%) and low roll-off of efficiencies even at ultralow doped concentration of 1%. These results demonstrate that BZC group is a good acceptor for developing high-performance TADF emitters. Graphical abstract: Image 1 Highlights: A novel twisted 3-benzoyl-4H-chromen-4-one (BZC) acceptor is reported. The unique structure of BZC group can endow the material with favorable molecular and stacking structures. BZC-based thermally activated delayed fluorescence emitter, BZC-PXZ, displays high performance in devices.